TJOKROAMINOTO'S INTEGRATION OF ISLAMIC PRINCIPLES AND SOCIALIST IDEALS : A HISTORICAL ANALYSIS - Farida Novita Rahmah; Lailatul Dzikriyah; Fadlilah Novia Rahmah (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2025)
This article aims to discuss Tjokroamninoto's thoughts on the discourse of Islam and socialism. The method used is the Historical method, which includes four stages, namely, heuristic, criticism, interpretation, and historiography. The main source used is Tjokroaminoto's own book, entitled "Islam and Socialism" published in 1924, then interpreted with other supporting sources. The result of this research is that Tjokro wrote the book Islam and Socialism in order to attract members to the big house of Sarekat Islam which accommodates all ideas. In this book, Tjokro appreciates Western socialist thought and combines it with the values of socialism in Islam. Tjokro argues that Islamic socialism can be realized based on obedience to God, fulfilling social and moral obligations to all humans regardless of status. The Prophet Muhammad as a messenger to the universe is a clear example. The Prophet Muhammad himself never practiced coercion in spreading socialism, did not engage in class warfare or call for the dictatorship of the proletariat. The Prophet reformed from the ground up by changing the nature and morals of his people. Key Word: Islam, Socialism, Tjokroaminoto